Direct evidence of amyloid precursor–like protein 1 trans interactions in cell–cell adhesion platforms investigated via fluorescence fluctuation spectroscopy - Dunsing, Valentin (Mol Biol Cell, 2017)
The amyloid precursor–like protein 1 (APLP1) is a type I transmembrane protein that plays a role in synaptic adhesion and synaptogenesis. Past investigations indicated that APLP1 is involved in the formation of protein–protein complexes that bridge the junctions between neighboring cells. Nevertheless, APLP1–APLP1 trans interactions have never been directly observed in higher eukaryotic cells. Here, we investigated APLP1 interactions and dynamics directly in living human embryonic kidney cells using fluorescence fluctuation spectroscopy techniques, namely cross-correlation scanning fluorescence correlation spectroscopy and number and brightness analysis. Our results show that APLP1 forms homotypic trans complexes at cell–cell contacts. In the presence of zinc ions, the protein forms macroscopic clusters, exhibiting an even higher degree of trans binding and strongly reduced dynamics. Further evidence from giant plasma membrane vesicles suggests that the presence of an intact cortical cytoskeleton is required for zinc-induced cis multimerization. Subsequently, large adhesion platforms bridging interacting cells are formed through APLP1–APLP1 trans interactions. Taken together, our results provide direct evidence that APLP1 functions as a neuronal zinc-dependent adhesion protein and allow a more detailed understanding of the molecular mechanisms driving the formation of APLP1 adhesion platforms.